2022
DOI: 10.1186/s12872-022-02793-5
|View full text |Cite
|
Sign up to set email alerts
|

TG/HDL-C ratio predicts in-hospital mortality in patients with acute type A aortic dissection

Abstract: Background In recent years, abnormalities in serum lipids and lipoproteins have been shown to be associated with cardiovascular disease risk. However, their prognostic value for acute type A aortic dissection is unclear. This study analyzed the correlation between triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) ratio and in-hospital mortality in patients with AAAD, and aimed to investigate the clinical significance of preoperative blood lipids and lipoproteins on the prognosis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The effect of BMI on perioperative mortality of ATAAD was extracted from 12 studies which included 5,522 patients. Single-center studies in China observed that mean BMI was associated with perioperative mortality of ATAAD, including 30-days mortality [ 21 ] (HR = 1.13, 95% CI: 1.03–1.25), in-hospital mortality [ 19 , 20 , 23 , 25 ] (OR = 1.15, 95% CI: 1.03–1.29, OR = 1.32, 95% CI: 1.03–1.70, HR = 2.61, 95% CI: 1.30–5.22 and OR = 1.09, 95% CI: 1.04–1.15). Consistently, different perioperative mortality of ATAAD was found between different BMI categories.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of BMI on perioperative mortality of ATAAD was extracted from 12 studies which included 5,522 patients. Single-center studies in China observed that mean BMI was associated with perioperative mortality of ATAAD, including 30-days mortality [ 21 ] (HR = 1.13, 95% CI: 1.03–1.25), in-hospital mortality [ 19 , 20 , 23 , 25 ] (OR = 1.15, 95% CI: 1.03–1.29, OR = 1.32, 95% CI: 1.03–1.70, HR = 2.61, 95% CI: 1.30–5.22 and OR = 1.09, 95% CI: 1.04–1.15). Consistently, different perioperative mortality of ATAAD was found between different BMI categories.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular inflammation also contributes to the development of abdominal aortic aneurysm (AAA), and HDL composition and functions have been reported to be altered in the disease [ 292 , 293 ]. The use of modified HDL as a surrogate biomarker of oxidative stress in AAA has also been proposed [ 294 ].…”
Section: Future Outlook and Perspectivesmentioning
confidence: 99%
“…Elevation in the triglycerides-high-density lipoprotein cholesterol (TG/HDL-c) ratio can be used as a marker of adiposity and an independent prognostic marker in patients with cardiovascular pathology; it has been shown to be correlated with abdominal obesity and higher body weight in healthy adults [ 121 ], but also with insulin resistance in some populations [ 122 ]. Studies have shown that there is an important correlation between TG/HDL-C ratio, in-hospital mortality, and major adverse cardiac events (MACEs) [ 123 , 124 ]. Patients with PAH usually have a low body mass index (BMI), but recent studies have highlighted elevated levels of circulating lipoproteins in such cases [ 125 ].…”
Section: Metabolic Biomarkersmentioning
confidence: 99%